Perbedaan Kejadian Tuberkulosis Pada Anak Dengan Pemberian Asi Eksklusif Dibandingkan Non Asi Eksklusif Di Balai Besar Kesehatan Paru Masyarakat (Bbkpm) Surakarta - Rahmawati, Rezita Oktiana; , Dr. Riana Sari Sp.P; , dr. Endang Widhiyastuti (2015)
Background : Tuberculosis is the infectious disease that became a global commitment by Millennium Development Global (MDGs). Factors that indicates the tuberculosis risk in children is positive tuberculosis contact from adult againts children, low socioeconomic, less income, population density, the state of nutrition, low education. Breastfeeding (ASI) is the nutrient for children when the baby, had antibodies to prevent infections such as Mycobacterium tuberculosis bacterial infection as cause of tuberculosis. Research Goals: Determine the difference in the incindence of tuberculosis in children with giving exclusive breastfeeding with non exclusive breastfeeding at the BBKPM Surakarta. Research Methods: This research using observational method with case control design. Subjects were children aged 1-7 year who diagnosed tuberculosis and asthma. The Independent variabel is giving exclusive breastfeeding and non exclusive breastfeeding. Number of sample is 50 people, 25 cases and 25 controls. Cases samples are the tuberculosis patient in the Pediatric BBKPM Surakarta. Control sampels are the asthma patient in the Pediatric BBKPM Surakarta. Data obtained from interview questionnaire. Analysis of data using Odds Ratio (OR). The Results : Statistic analyse is OR 2,25 (OR>1) means the children on giving exclusive breastfeeding risk 2,25 times more likely contract tuberculosis than in children with non exclusive breastfeeding and CI 95% (0,726-6,976) and p is 0,129 (p<0,005), where not showing significant. Conclusion :. The result showed that the the children on giving exclusive breastfeeding risk 2,25 times more likely contract tuberculosis than in children with non exclusive breastfeeding although statistic analyse was not showing significant because of age factor, low income and adult TB contact were influenced.